Gait Speed and Mobility Disability: Revisiting Meaningful Levels in Diverse Clinical Populations. Issue 5 (2nd April 2018) - Miller, Michael E.; Magaziner, Jay; Marsh, Anthony P.; Fielding, Roger A.; Gill, Thomas M.; King, Abby C.; Kritchevsky, Stephen; Manini, Todd; McDermott, Mary M.; Neiberg, Rebecca; Orwig, Denise; Santanasto, Adam J.; et al.
Abstract : Objectives: To investigate the heterogeneity of clinically meaningful levels of gait speed relative to self‐reported mobility disability (SR‐MD). Design: Five longitudinal studies with older adults in different health states (onset of acute event, presence of chronic condition, sedentary, community living) were used to explore the relationship between gait speed and SR‐MD. Setting: Lifestyle Interventions and Independence for Elders Pilot (LIFE‐P), LIFE, Trial of Angiotensin‐Converting Enzyme Inhibition and Novel Cardiovascular Risk Factors (TRAIN), Baltimore Hip Fracture Study (BHS2), Invecchiare in Chianti (InCHIANTI). Participants: Individuals aged 65 and older (N=3, 540): sedentary, community dwelling (LIFE‐P/LIFE), with hip fracture (BHS2), random population‐based sample (InCHIANTI), high cardiovascular risk (TRAIN). Measurements: Usual‐pace gait speed across 3 to 4 m and SR‐MD, defined as inability to walk approximately 1 block or climb 1 flight of stairs. Results: The mean gait speed of participants without SR‐MD was greater than 1.0 m/s in InCHIANTI and TRAIN, 0.79 m/s in LIFE‐P/LIFE, and 0.46 m/sec in BHS2. Of individuals with SR‐MD, mean gait speed was 0.08 m/s slower in LIFE‐P/LIFE, 0.19 m/s slower in TRAIN, 0.22 m/s slower in BHS2, and 0.36 m/s slower in InCHIANTI. The optimal gait speed cutpoint for minimizing SR‐MD misclassification rates ranged from 0.3 m/s in BHS2 to 1.0 m/s in TRAIN. In longitudinal analyses, development of SR‐MD was dependent on initial gait speed and change in gait speed (p<.001). Conclusion: The relationship between absolute levels of gait speed and SR‐MD may be context specific, and there may be variations between populations. Across diverse clinical populations, clinical interpretations of how change in usual pace gait speed relates to development of SR‐MD depend on where on the gait speed continuum change occurs.